Endoscopic Papillectomy for Major and Minor Papillary Adenoma in Familial Adenomatous Polyposis. Issue 3 (March 2019) - Ahmed, Moiz; Philipose, Jobin; Hunton, Andrew; Andrawes, Sherif
Abstract : ABSTRACT: Ampullary adenomas can occur sporadically or in the patients with adenomatous polyposis syndrome, including familial adenomatous polyposis (FAP) and MUTYH -associated polyposis. The potential for malignant transformation is high in the setting of FAP. Although endoscopic resection of major papillary adenoma has been well described, minor papilla adenomas are exceptionally rare. This is the second documented case of an endoscopic papillectomy in a patient with FAP with simultaneous ampullary adenoma of the major and minor papilla.